Apakah Investor Milenial Penyebab Terbentuknya Teknikal Anomali di Pasar Modal Indonesia? - Shafiera Lazuarni; William Wendy Ary; Try Wulandari; Emilda Emilda (MBIA, 2022)
This study aims to examine the role of millennial investors' simplification behavior (heuristic) on the formation of technical anomalies in the capital market and the role of these anomalies on investment performance. The method of the data analysis used the SEM (Structural Equation Modeling) method with the WarpPLS analysis tool. The Variance Accounted For (VAF) method was added in this study as an additional test to explore whether technical anomalies can mediate the effect of heuristics on investment performance. The results proved that the heuristic behavior (availability, representativeness, and hindsight) of millennial investors is one of the factors causing technical anomalies in the capital market, except for the availability heuristic. The limitations of this study were the first measurement items/items used were minimal, amounting to two to four items for each construct. Second, this study could not detail how millennial investors behaved when selling or buying shares. This study is essential as investors can understand their investment behavior and they can make better decisions. Further, providing information regarding the behavior of millennial investors to the government because the millennial generation is an essential key in encouraging them to be at the forefront of the Indonesian economy. The implication is that the government can develop strategies and policies to increase the involvement of the millennial generation in investing in the capital market. Keywords: Investor Behavior, Millennial Investors, Anomalies, Heuristics, Capital Market Abstrak Penelitian ini bertujuan menguji peran perilaku penyederhanaan (heuristik) investor milenial terhadap terbentuknya teknikal anomali di pasar modal dan peran anomali tersebut terhadap kinerja investasi. Metode analisis data menggunakan metode SEM (Structural Equation Modeling) dengan alat analisis WarpPLS. Metode Variance Accounted For (VAF) juga ditambahkan dalam penelitian ini sebagai ujian tambahan untuk mengeksplorasi apakah teknikal anomali mampu memediasi pengaruh antara heuristik terhadap kinerja investasi. Hasil penelitian menunjukkan bahwa perilaku heuristik (availability, representativeness, dan hindsight) investor milenial terbukti menjadi salah satu faktor penyebab terjadinya teknikal anomali di pasar modal, kecuali availability heuristik. Keterbatasan penelitian ini pertama item pengukuran/item yang digunakan sangat terbatas berjumlah dua hingga empat item untuk masing-masing konstruk. Kedua, penelitian ini tidak mampu menangkap secara detail bagaimana perilaku investor milenial secara terpisah saat menjual atau membeli saham. Penelitian ini penting dilakukan agar investor dapat memahami perilaku investasi mereka sehingga mampu mengambil keputusan lebih baik. Kedua, memberikan informasi terkait perilaku investor milenial ke pemerintahan karena generasi milenial menjadi kunci penting dalam mendorong mereka menjadi garda terdepan dalam perekonomian Indonesia. Implikasinya pemerintah dapat menyusun strategi dan kebijakan dalam peningkatan keterlibatan generasi milenial dalam berinvestasi di pasar modal. Kata Kunci: Perilaku Investor, Investor Milenial, Anomali, Heuristik, Pasar Modal